Towards numeracy literacy development: A single-case study on the use of the living book homeschooling model - Andi Harpeni Dewantara; Farida Agus Setiawati; Sari Saraswati (IKIP Siliwangi and I-MES, 2023)
Public schools are not always believed to be able to support the development of an individual's potential comprehensively. Homeschooling, an educational program where students learn from home, is currently an alternative education. This study aims to reveal why parents choose to homeschool their children and describe how a homeschooler parent as a single tutor develops her child’s numeracy literacy skills in living book homeschooling. This research is a holistic single-case study with two subjects: a homeschooler (J) and his mother (UPL) as the tutor. Data were collected through in-depth interviews and document analysis of J’s learning activities. Thematic analysis with Atlas.ti software was employed. Findings reveal that the parents’ main reasons for homeschooling are dissatisfaction with public school instruction and flexibility to comprehensively develop homeschoolers’ skills. In addition, the integration of RME (Realistic Mathematics Education) in the living book homeschooling model is a very powerful support to students’ literacy numeracy development. Practically, there are three main strategies implemented; the use of real contexts and concrete teaching aids, as well as an emphasis on conceptual understanding and high-order thinking skills.